Designing a Multimer Allergen for Diagnosis and Immunotherapy of Dog Allergic Patients - Nilsson, Ola B.; Neimert-Andersson, Theresa; Bronge, Mattias; Grundström, Jeanette; Sarma, Ranjana; Uchtenhagen, Hannes; Kikhney, Alexey; Sandalova, Tatyana; Holmgren, Erik; Svergun, Dmitri; Achour, Adnane; van Hage, Marianne; et al. (PLOS ONE, 2014)
Background Dog dander extract used for diagnosis and allergen-specific immunotherapy is often of variable and of poor quality. Objective To assemble four well-established dog allergen components into one recombinant folded protein for improved diagnosis and vaccination of allergy to dog. Methods A linked molecule, comprising the four dog lipocalin allergens Can f 1, Can f 2, Can f 4 and Can f 6 was constructed. The tetrameric protein was structurally characterized by small angle X-ray scattering, and compared with each single recombinant lipocalin allergen or an equimolar mix of the four allergens by analytical size exclusion chromatography, circular dichroism, allergen-specific IgE in serum by ELISA and allergen-dependent capacity to activate basophils. The immunogenicity of the fusion protein was evaluated in immunized mice by assessing splenocyte proliferation and antibody production. Results The linked tetrameric construct was produced as a soluble fusion protein, with the specific folds of the four individual allergens conserved. This multi-allergen molecule was significantly more efficient (p<0.001) than each single recombinant allergen in binding to dog-specific IgE, and the epitope spectrum was unaffected compared to an equimolar mix of the four allergens. Basophil degranulation revealed that the biologic activity of the linked molecule was retained. Immunization of mice with the linked construct induced comparable allergen-specific IgG responses with blocking capacity towards all included allergens and generated comparably low T-cell responses. Conclusion We provide the first evidence for a linked recombinant molecule covering the major dog allergens for potential use in diagnostics and allergy vaccination of dog allergic patients.